How can evolutionary and biological anthropologists engage broader audiences?. Issue 4 (9th March 2021) - Jones, James Holland; Pisor, Anne C.; Douglass, Kristina G.; Bird, Rebecca Bliege; Ready, Elspeth; Hazel, Ashley; Hackman, Joseph; Kramer, Karen L.; Kohler, Timothy A.; Pontzer, Herman; Towner, Mary C.
Abstract: Objectives: With our diverse training, theoretical and empirical toolkits, and rich data, evolutionary and biological anthropologists (EBAs) have much to contribute to research and policy decisions about climate change and other pressing social issues. However, we remain largely absent from these critical, ongoing efforts. Here, we draw on the literature and our own experiences to make recommendations for how EBAs can engage broader audiences, including the communities with whom we collaborate, a more diverse population of students, researchers in other disciplines and the development sector, policymakers, and the general public. These recommendations include: (1) playing to our strength in longitudinal, place‐based research, (2) collaborating more broadly, (3) engaging in greater public communication of science, (4) aligning our work with open‐science practices to the extent possible, and (5) increasing diversity of our field and teams through intentional action, outreach, training, and mentorship. Conclusions: We EBAs need to put ourselves out there: research and engagement are complementary, not opposed to each other. With the resources and workable examples we provide here, we hope to spur more EBAs to action.